Towards the creation of an Entrepreneurial Society in Oman The impact of Government intervention to facilitate the development and success of small and medium enterprises in Oman - Al Shauibi, Khalid (2007)
This research will examine the current Small and Medium Enterprise (SME) support strategy in Oman and will define the strengths and weaknesses of the entrepreneurial environment by applying a five dimensional conceptual framework to analyze the structural problems related to the business environment for SME's in Oman. The five dimensions which define the entrepreneurial environments are; government policies and procedures, socio-economic situation, entrepreneurial and business skills, financial support to business, and the non-financial support to businesses.